The influence of physical activity on mental well-being in college students: a systematic review - Li, Ruochen; Huang, Rong (Frontiers in Psychology, 2025)
IntroductionPhysical activity (PA) is widely recognized for its benefits on mental well-being, yet evidence regarding its specific impact on college students remains insufficient. This systematic review investigates the association between PA and mental well-being in college students, focusing on key outcomes such as self-esteem, depression, and subjective well-being.MethodsA comprehensive search was conducted in Web of Science and Scopus up to August 2024 using Boolean operators (e.g., “physical activity,” “mental well-being,” “college students”). Inclusion criteria targeted studies with quantitative or qualitative data on PA and well-being outcomes in higher education populations. After screening 746 abstracts and applying exclusion criteria (e.g., non-college populations, tangential PA focus), 28 articles were selected for full-text review following PRISMA guidelines.ResultsThe review synthesized findings across three dimensions: (1) PA positively correlates with self-esteem, though gender and cultural biases may influence outcomes; (2) weak negative correlations (r < 0.2) were observed between PA and depression, indicating PA’s potential but non-exclusive role; (3) PA enhances subjective well-being, particularly through intrinsic motivation and structured activities. However, heterogeneity in well-being definitions and measurement tools limited comparability.DiscussionWhile PA demonstrates a positive association with mental well-being in college students, inconsistencies in study designs and mechanistic explanations highlight the need for future research to clarify causal pathways, differentiate PA types/intensity, and standardize well-being metrics. Universities should prioritize PA promotion to support student well-being during this critical developmental stage.